Sintering behaviour of nano-crystalline γ-Al2O3 powder without additives at 2-7 GPa - Kuskonmaz, Nilgun; Can, Nedret; Can, Antionette; Sigalas, Lakovos (ELSEVIER SCI LTD, 2011)
Al2O3 ceramics were fabricated without additives under high pressure (2-7 GPa) at different temperatures (600-1200 degrees C) using nanocrystalline alumina powder with metastable gamma-Al2O3 phase as the starting material. It was shown that high pressure increases the nucleation rate while reducing the growth rate of the transformed a phase so that its grain size decreases and nano-scale grains in the sintered structure can be achieved. On the other hand the sintered samples at 7 GPa and high temperature (1000 degrees C) have shown micron-scale large grain sizes compared to those sintered at lower pressures, for the same temperature and sintering time. This could be attributed to the higher input energy in the system at high pressure and high temperature conditions, thereby reaching the final stage in sintering more quickly. In this work, the best combination of grain size (similar to 200 nm) and density (98.0% TD) was obtained under the sintering condition of 1000 degrees C at 7 GPa with a holding time of 1 min. Thus for high pressure/high temperature conditions, the sintering time should be reduced to prevent grain growth. (C) 2010 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Sintering; Grain Size; Al2O3; HIGH-PRESSURE COMPACTION; ALUMINA; Materials Science